Implementing Chinese student support services at a German technical university - Auschner, Eika; Jiang, Lili (Journal of International Students, 2025)
In this study, we investigate the challenges that Chinese students face at a German technical university, highlighting key obstacles such as language barriers, cultural differences, and limited trust in institutional support. Through thematic analysis of qualitative data collected in 20 in-depth interviews with Chinese students enrolled at a German technical university and following a biographical narrative approach, the findings underscore the importance of tailored support measures. The proposed interventions focus on academic success, psychological well-being, and career preparation, providing a comprehensive framework for fostering an inclusive and supportive educational environment. These insights aim to enhance the integration and overall experience of Chinese students in Germany.